Sources of glucose production in cirrhosis by 2H2O ingestion and 2H NMR analysis of plasma glucose - Perdigoto, Rui (2003)
Plasma glucose 2H enrichment was quantified by 2H NMR in patients with cirrhosis (n=6) and healthy subjects (n=5) fasted for 16 h and given 2H2O to ~0.5% body water. The percent contribution of glycogenolysis and gluconeogenesis to glucose production (GP) was estimated from the relative enrichments of hydrogen 5 and hydrogen 2 of plasma glucose. Fasting plasma glucose levels were normal in both groups (87±7 and 87±24 mg/dl for healthy and cirrhotic subjects, respectively). The percent contribution of glycogen to GP was smaller in cirrhotics than controls (22±7% versus 46±4%, P<0.001), while the contribution from gluconeogenesis was larger (78±7% versus 54±4%, P<0.001). In all subjects, glucose 6R and 6S hydrogens had similar enrichments, consistent with extensive exchange of 2H between body water and the hydrogens of gluconeogenic oxaloacetate (OAA). The difference in 2H-enrichment between hydrogen 5 and hydrogen 6S was significantly larger in cirrhotics, suggesting that the fractional contribution of glycerol to the glyceraldehyde-3-phosphate (G3P)-moiety of plasma glucose was higher compared to controls (19±6% versus 7±6%, P<0.01). In all subjects, hydrogens 4 and 5 of glucose had identical enrichments while hydrogen 3 enrichments were systematically lower. This reflects incomplete exchange between the hydrogen of water and that of 1-R-dihydroxyacetone phosphate (DHAP) or incomplete exchange of DHAP and G3P pools via triose phosphate isomerase.